Length Frequency and Sex Ratio of Bullet Tuna (Auxis rochei) Landed at Ternate Archipelago Fishing Port, Indonesia - Iksan, Kusdi Hi; Irham, Irham; Susanto, Adi Noman; Ahmad, Aditiyawan; Alhadad, M. Said; Kadir, Masykhur Abdul Kadir; Rahman, Nurdawia W. (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
This study aims to analyze the length distribution and sex ratio of bullet tuna (Auxis rochei) landed at Ternate Archipelago Fishing Port Ternate (PPN Ternate). Sampling was conducted in June and July 2024 with 100 fish per month. Observations included total length measurements and sex identification to determine size distribution patterns and sex composition. The results showed that male fish in June had the highest frequency at class interval of 190-201 mm, and in July it shifted to class interval 226-237 mm. Meanwhile, female fish in June were dominant in the class interval of 201-210 mm, and in July increased to the class interval of 231-230 mm. The sex ratio in June was 1:1.22 (male:female), while in July it was 1:0.82. The results of the chi-square test showed that the difference in sex ratio was not statistically significant (p > 0,05), so the population was considered to have a balanced sex composition. This finding is in line with several previous studies in the Indonesian region that showed variations in size structure and sex ratio of Auxis rochei influenced by seasonality, reproductive migration, and fishing activity. This study provides important basic information to support sustainable management of bullet tuna (Auxis rochei) resources in North Maluku waters.